Opioid and cocaine use among primary care patients on buprenorphine—Self-report and urine drug tests. (1st November 2018) - Bagley, Sarah M.; Cheng, Debbie M.; Winter, Michael; Alford, Daniel P.; LaBelle, Colleen; Walley, Alexander Y.; Samet, Jeffrey H.
Highlights: Truthful disclosure of opioid and cocaine use increases with time in treatment for opioid use disorder (OUD). Urine drug tests provide useful information to clinicians treating OUD. Further work should explore optimal protocols for urine drug testing in office-based addiction treatment (OBAT) in primary care. Abstract: Background: Urine drug tests (UDTs) are recommended to monitor patients treated for opioid use disorder in primary care. The aims are to (1) estimate the frequency of self-report and UDT results of opioid and cocaine use and (2) evaluate the association between treatment time with non-disclosure of opioid or cocaine use and having a positive UDT. Methods: We conducted a retrospective review of patients enrolled in a primary care-based buprenorphine program between January 2011–April 2013. We describe three clinical visits types: no disclosure of opioid/cocaine use and positive UDT; disclosure of opioid or cocaine use and a negative or positive UDT; and no disclosure of opioid or cocaine use and a negative UDT. We fit generalized estimating equations logistic regression models to evaluate whether treatment time is associated with non-disclosure of opioids or cocaine use and a positive UDT. Results: Among all UDT results (n = 1755) from 130 patients, 10% were positive for illicit opioids and 4% for cocaine. Among UDTs with illicit opioid or cocaine positive results, in 57% and 76% of these scenarios, the patient did not disclose. The odds of non-disclosure and having a positive UDT was higher in the first 180 days for opioids and 90 days for cocaine. Conclusion: Among primary care patients treated with buprenorphine, a small but substantial percentage of UDTs were cocaine or opioid positive. As treatment time increased, non-disclosure was less common but persisted even after six months. Among primary care patients treated with buprenorphine, UDTs contribute information to optimize clinical care.